Gas chromatography‐mass spectrometry based metabolomics profile of hippocampus and cerebellum in mice after chronic arsenic exposure. Issue 2 (29th October 2018) - Mo, Ting‐Ting; Dai, Hua; Du, Hang; Zhang, Rui‐Yuan; Chai, Ke‐Ping; An, Yao; Chen, Ji‐Ji; Wang, Jun‐Ke; Chen, Zi‐Jin; Chen, Cheng‐Zhi; Jiang, Xue‐Jun; Tang, Rong; et al.
Abstract: Intake of arsenic (As) via drinking water has been a serious threat to global public health. Though there are numerous reports of As neurotoxicity, its pathogenesis mechanisms remain vague especially its chronic effects on metabolic network. Hippocampus is a renowned area in relation to learning and memory, whilst recently, cerebellum is argued to be involved with process of cognition. Therefore, the study aimed to explore metabolomics alternations in these two areas after chronic As exposure, with the purpose of further illustrating details of As neurotoxicity. Twelve 3‐week‐old male C57BL/6J mice were divided into two groups, receiving deionized drinking water (control group) or 50 mg/L of sodium arsenite (via drinking water) for 24 weeks. Learning and memory abilities were tested by Morris water maze (MWM) test. Pathological and morphological changes of hippocampus and cerebellum were captured via transmission electron microscopy (TEM). Metabolic alterations were analyzed by gas chromatography‐mass spectrometry (GC‐MS). MWM test confirmed impairments of learning and memory abilities of mice after chronic As exposure. Metabolomics identifications indicated that tyrosine increased and aspartic acid (Asp) decreased simultaneously in both hippocampus and cerebellum. Intermediates (succinic acid) and indirect involved components of tricarboxylic acid cycle (proline, cysteine, and alanine) were found declined in cerebellum, indicating disordered energy metabolism. Our findings suggest that these metabolite alterations are related to As‐induced disorders of amino acids and energy metabolism, which might therefore, play an important part in mechanisms of As neurotoxicity.